Breast Cancer and Associated Risk Factors: A Comprehensive Review - Mohammed Ail Al Barak et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Breast cancer is the most common malignancy affecting women worldwide, with a rising incidence in both developed and developing countries. This review explores the associated risk factors for breast cancer, including genetic predisposition, lifestyle habits, hormonal influences, and environmental exposures. Understanding these risk factors is crucial for prevention, early detection, and targeted interventions. Recent studies have emphasized the role of modifiable risk factors such as diet, physical activity, and obesity alongside non-modifiable factors like age, family history, and genetic mutations. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/282 https://doi.org/10.5281/zenodo.14502506